Water injection control modelling by using model-based calibration - Kamaludin, Khairul Khusairi; Mamat, Aman Mohd Ihsan; Mohamed, Zulkifli; Wan Salim, Wan Saiful-Islam (Institute of Advanced Engineering and Science, 2022)
This study presents the development of water injection system for turbocharged spark ignition engine. The water injection control system is built for turbocharged spark ignition (SI) engine where water was injected at the intake port just before the throttle body. The data was collected from the simulation through the GT-Power software to determine the optimized injection output for the engine. Single-stage statistical engine responses and boundary models were established by using Model-Based Calibration (MBC) Toolbox. Control system was built using Simulink and simulation tests were conducted based on the speed and throttle position as the variables. The highest value of brake torque achieved in the GT-Power simulation was taken as the base value to determine the injection amount. The mean value of the predicted injection was recorded at 12.29 g/s while the variance of the predicted injection to the optimized injection was below 1%. The control system was simulated with the set predicted injection and the standard deviation of the predicted injection was 1.18. The control system simulation recorded a low percentage of 0.04% variance to the optimized injection with the pulse width modulation signal. The control system is ideal to be constructed and tested on actual engine test bed.